The Evolution and Intellectual Structure of Local Wisdom Research in Indonesian Education: A Fifteen-Year Bibliometric and Systematic Analysis (2010–2025) - Djedjen Djedjen; Dede Trie Kurniawan; Yunus Abidin (Journal of Innovation in Educational and Cultural Research, 2026)
The concept of local wisdom has become a significant strategic basis for culturally based education in Indonesia, though the structure of intellectual form and the developmental course of research in this area have yet to be fully synthesized. The paper explores the development and intellectual architecture of local wisdom research in Indonesian education between 2010 and 2025 through an inter-woven bibliometric and systematic approach. Based on PRISMA procedures, 132 studies were selected from 575 records of Scopus-indexed journal articles. The growth of publications, most popular journals, institutional productivity, and international contributions were analyzed using bibliometric mapping, and qualitative thematic synthesis identified the prevalent research clusters and theoretical orientations. According to the findings, a significant growth trend can be observed in recent years, and scholarship is concentrated mostly in Indonesian institutions, with a predominance of the sociocultural and constructivist approaches. Five important thematic areas were identified, reflecting an inclination toward pedagogical application. The paper finds that although the field is growing very fast, it is nationally confined and theoretically fragmented. This study provides intellectual scaffolding and strategic pathways for more rigorous and globally active scholarship by mapping the intellectual architecture of the field.